Efficacy and safety of DPL500 combined with tacrolimus ointment in the treatment of type Ⅰ rosacea - Danbin SU; Qilin LI; Yingyun REN; Yahui LIU; Jiaping LI (Pifu-xingbing zhenliaoxue zazhi, 2024)
Objective To evaluate the efficacy and safety of DPL500 combined with tacrolimus ointment in the treatment of type Ⅰ rosacea. Methods A total of 80 patients with type Ⅰ rosacea were enrolled at the Foresea Life Insurance Guangzhou General Hospital from October 2020 to September 2022, and randomly divided into the observation and control groups, 40 cases per group. The observation group was treated with DPL500 once a month and 0.1% tacrolimus ointment twice-daily for 3 months, while the control group was treated with 0.1% tacrolimus ointment alone. The efficacy and safety were compared between the two groups. Results Following the treatment, the total effective rate was higher in the observation group than in the controls (97.50% vs. 80.00%, χ2=4.51,P<0.05). More rapid improvements in skin flushing, telangiectasia, erythema and skin sensitivity were observed in the observation group compared to the controls (P<0.05). Although the baseline subjective and objective scores did not differ significantly between the two groups (P>0.05), both subjective and objective scores in the observation group were significantly lower than that in the controls after 30-, 60- and 90-day treatment (P<0.05). However, adverse reactions were comparable between the two groups (χ2=0.18,P=0.672). Conclusions DPL500 combined with tacrolimus ointment is effective and safe in the treatment of type Ⅰ rosacea. It can quickly improve the facial symptoms.